Boruta algorithm–guided antibiotic selection in antibiotic-loaded bone cement for diabetic foot ulcers: microbiota and susceptibility analysis - Zhang, Yi; Sun, Xingyu; Wu, Maochun; Tang, Xin (Frontiers in Pharmacology, 2025)
BackgroundDiabetic foot is one of the serious complications of diabetes mellitus, and diabetic foot ulcer (DFU) infection is often fatal to patients. As a relatively new method, antibiotic bone cement treatment of diabetic foot is beneficial to many patients with diabetic foot infection (DFI). The aim of this study is to analyze the composition of DFU wound microbiota and to screen antibiotics with better efficacy to add to bone cement for the treatment of DFI.MethodsWe collected the exudates from DFU wounds of patients for bacterial culture and drug susceptibility test, and classified and analyzed the composition of bacterial microbiota. For drug susceptibility test results, we first screened the antibiotics by using the Boruta algorithm prediction model and then performed sensitivity analysis based on age and gender factors.ResultsAccording to this study, age was a significant factor in the cumulative sensitivity of bacteria to antibiotics added with bone cement. In the bacterial microbiota of DFU wounds, Gram-positive bacteria accounted for a relatively high proportion, and the main species was Staphylococcus aureus. Based on the analysis, the better choices of antibiotics were Gentamicin (GEN) and Tobramycin (TOB) for Gram-negative bacteria and Moxifloxacin (MFX), Ampicillin (AMP) and Quinupristin-dalfopristin (QDA) for Gram-positive bacteria.ConclusionIn the treatment of DFI, Gram-positive bacteria infection is more common in clinical practice, especially anti-infective treatment against Staphylococcus aureus needs to be paid attention to. Based on our findings, it is advised that the DFU population who requires bone cement antibiotic treatment be treated according to age, with GEN and TOB being recommended for Gram-negative bacteria and MFX, AMP, and QDA for Gram-positive bacteria.